Pemberdayaan Ekonomi Masyarakat Dalam Manajemen Zakat Berbasis Digital - Mutmainah, Mutmainah; Susanto, Andik; Alfianto Rizkaputra, Fergiawan; Satya Pradana, Deva (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2025)
The sophistication of technology that facilitates all transactions does not make people aware of the zakat that they must issue. Even though it has been written in the Quran and the Law of the Republic of Indonesia, it does not make people who have met the requirements of zakat mandatory to just issue zakat. In addition, the public's ignorance about the zakat application that makes it easier for them, not all people know it. Like the people in Glonggong Village, Madiun Regency. This attracts academics to socialize about digital-based zakat management in the region. This socialization activity was carried out by inviting PKK women. These mothers are one of the actors who take part in financial management in the household. The activity was carried out by lecture and discussion method. But it is possible to receive discussions about the management of zakat outside of socialization activities on that day. The lecture method was carried out in the Hall of the Gronggong Village Office. This activity was attended by 25 women of the Glinggong Village PKK. The results of the implementation of the activity showed the high enthusiasm of the socialization participants. This is shown by the large number of participants who asked questions. This public enthusiasm is expected to be followed up by paying zakat digitally to make it easier for the community, the committee, and its transparency.